Mapping research trends in obsessive-compulsive disorder before and after the COVID-19 pandemic: a bibliometric analysis focusing on its molecular mechanisms - Inoue, Yuito; Ichise, Nobutoshi; Ukai, Wataru; Shinozaki, Jun; Ogawa, Toshifumi; Karaushi, Takuro; Tanaka, Marenao; Akiyama, Yukinori; Furuhashi, Masato; Kuno, Atsushi; Sato, Tatsuya (Frontiers in Psychiatry, 2025)
Obsessive-compulsive disorder (OCD) is a psychiatric disorder that primarily develops during adolescence, and is characterized by obsessive thoughts and compulsive behaviors. Although multiple factors including heredity, environment, and abnormalities in neural networks and synapses are involved in the onset and exacerbation of OCD, their underlying molecular mechanisms have not been fully elucidated. In addition, recent studies have demonstrated that the novel coronavirus disease (COVID-19) pandemic worsened OCD phenotypes. Hence, this global crisis may have changed the field of molecular-focused OCD research. We conducted a brief bibliometric analysis to investigate changes in prevalent topics in molecular-focused OCD research before (2015-2019) and after (2020-2025) the COVID-19 pandemic using Web of Science and VOSviewer. “Schizophrenia” and “metaanalysis” remained highly ranked terms in molecular-focused OCD research. In terms of neurotransmitters, the term “serotonin” became more prevalent than “dopamine” after the COVID-19 pandemic. In addition, research interest shifted toward younger populations, and there was a noticeable increase in terms related to neural networks such as “connectivity”. However, only a few specific molecular mechanisms or cellular physiological pathways by which COVID-19 exacerbates OCD have been identified. To address this gap, an additional post hoc analysis focusing on inflammation-related terms was conducted, revealing the emergence of “oxidative stress” and “c-reactive protein” in studies published after the COVID-19 pandemic. The findings of this study highlight several potential clues for elucidating the pathophysiology of OCD and identifying aggravating factors such as COVID-19, while also emphasizing the importance of continued molecular-focused research to establish novel therapeutic targets.